Differentiation of Learning Achievement Towards Children's Behavior - Saipul Hadi (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2021)
Having a noble character and being responsible is one of the goals of national education as stated in the law. However, in reality the unfavorable behavior displayed by students when they are at school or at home is a problem for teachers and even parents. This study intends to explore children's behavior through the question of whether there are differences in students who have high, medium, and low scores in the Akidah Akhlak Subject on their daily behavior at Madrasah Ibtidaiyah Negeri II Kab. Banjar. The research method is descriptive qualitative by taking samples of grade IV and V students in the first semester who have received high, medium, and low scores in the Akidah Akhlak Subject and then taking 20% of the two classes randomly. Data collection techniques with documentation, observation and distributing questionnaires to students. The data analysis technique uses reduction and conclusion. The results show that there are differences in the behavior of students who have high, medium, and low scores in the Akhlak Akidah Subjects. These behaviors appear in the politeness aspect towards the teacher, then in the aspect of getting along with friends.